Mantenimiento del módulo didáctico de prácticas electroneumáticas del Laboratorio de Automatización y control de la Facultad de Ingeniería Electrónica, Mecánica y Biomédica de Universidad Antonio Nariño Sede Cartagena (2023)
Antonio Narino University, It has a didactic test bank important tool in theoretical development practice for students of the Faculty of Electronic, Mechanical and Biomedical Engineering time when it is required simulations or laboratory practices. By Consequently, it is proposed to carry out a project of electromechanical maintenance, which consists in the current assessment and subsequent maintenance of its components, prepare the plan of preventive maintenance and testing of operation to deliver the equipment to satisfaction. It is intended to carry out maintenance of the equipment and is expected to leave it enabled so that students can carry out their electropneumatic practices at satisfaction.